Evapotranspiration of Indonesia Tropical Area - Marganingrum, Dyah; Santoso, Heru (Universitas Diponegoro, 2019)
Indonesia is an archipelago country with a tropical climate. The region of Indonesia is quite large and located between two continents (Asia and Australia) and between two oceans (Indian and Pacific), making the territory of Indonesia has a unique climate pattern. One of the climate variables that quite important to be studied in this chapter is evapotranspiration. The Thornthwaite method was used to estimate potential evapotranspiration based on average air temperature. The relationships between evapotranspiration, precipitation, and elevation were then examined. Besides, temperature variations that affect climate patterns between monsoonal and equatorial regions were compared, between the mainland and small islands, and between mountain and coastal area. The impact of global warming was also examined on the climate and potential evapotranspiration of the Indonesian region. Data analysis showed that evapotranspiration correlates weakly with precipitation, and the contrary, the evapotranspiration correlates strongly with elevation, with correlation indices of 0.02 and 0.89, respectively. The study confirmed that air temperature is the primary controlling variable of the evapotranspiration in this very heterogeneous landscape. Under a global temperature increase of 1.5 Â°C above the pre-industrialized year (1765), the evapotranspiration is expected to increase in a range from 4.8 to 11.1%. In general, the excess of water to restore soil moisture in the future tends to decrease, i.e., drier.